MODAL BUDAYA PADA KOMUNITAS SEKOLAH ADAT DI KECAMATAN SIANJUR MULA MULA KABUPATEN SAMOSIR - Romartu Situngkir; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Sekolah Adat Rumah Belajar Sianjur mula mula have started to become reactions to the decline of young people who no longer take pride in identity as batak people, based on the declining reactions of young people who love their own culture. Because That Rumah Belajar founded as a community that is engaged in cultural and cultural education and love of the environment. This indigenous school focuses on teaching the young people who are the next generation of nations to know their own culture. The purpose of this research is to see how a picture of cultural capital in the Rumah Belajar Sianjur Mula Mula district Samosir Regency. The study use a qualitative technique by using observation techniques, interviews and documentation on all activities conducted by Rumah Belajar. The result of this research is revealing a volunteer background teaching in Rumah Belajar is a desire to dedicate self, to increase knowledge and also to preserve culture through the younger generation. In this study, it also reveals the cultural capital available in home volunteer Rumah Belajar is the result of a legacy of learning to parents and customs leaders, which are the subjects of teaching. The habbits adopted in this Rumah Belajar is the use of a holster, to say horas,  to pray, to say batak days, studying and praying, and after studying, reenacing say horas and speak the days of the Batak. Indigenous school . Rumah Belajar Sianjur Mula Mula seriously to make reproduction cultural with happy study. Key words: education custom, Rumah Belajar, cultural capital